STEREOCHEMISTRY - RACEMIC MODIFICATION, RESOLUTION, AND ITS IMPORTANCE WITH RECENTLY USED OPTICALLY ACTIVE DRUGS. - Baregama, Chetna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Stereochemistry involves the study of the relative spatial arrangement of atoms that form the structure of molecules and their manipulation. An important branch of stereochemistry is the study of chiral molecules. Optical activity is the ability of a chiral molecule to rotate the plane of plane-polarized light, measured using a polarimeter. Racemic modification and resolution, both processes are very important in stereochemistry. A mixture of equal parts of enantiomers is called a racemic modification. The process of separating a racemate into pure enantiomers is known as resolution. Recently, various optically active drugs are used for the treatment for various diseases. In these drugs, some are used as mixture of enantiomers and some used as single enantiomer. For preparation of optically active drugs, racemic modification and resolution processes are generally used. Hence, this is very important to know about various steps and types of processes used for the same. Racemic modification is advantageous where racemates have more therapeutic advantages than single isomers. Resolution is advantageous where single entiomer is used for treatment because single enantiomers have less complex and more selective pharmacodynamic profile as compared to racemic mixture so have lesser adverse drug reactions, improved therapeutic profile, less chances of drug interactions than racemic mixtures. Recently used optically active drugs are amlodipine, atenolol, cetirizine, ketamine, metoprolol, omeprazole, pantoprazole, salbutamol, propranolol, clopidogrel, rabeprazole, citalopram, ibuprofen, ketoprofen, zopiclone, etodolac, salbutamol, and nateglinide.